COMMUNITY-EQUIPOISE AND THE ETHICS OF RANDOMIZED CLINICAL TRIALS - Gifford, Fred (Bioethics, 1995)
This paper critically examines a particular strategy for resolving the central ethical dilemma associated with randomized clinical trials (RCTs) — the “community equipoise” strategy (CE). The dilemma is that RCTs appear to violate a physician's duty to choose that therapy which there is most reason to believe is in the patient's best interest, randomizing patients even once evidence begins to favor one treatment. The community equipoise strategy involves the suggestion that our judgment that neither treatment is to be preferred (that there obtains a state of “equipoise”) is to be assessed according to a community rather than an individual standard. Thus, though a physician may personally believe that there is some reason to prefer one treatment, patients can legitimately be randomized if there remains disagreement in the community of medical professionals. Rationales in favor of this conception include the following: (i) medical knowledge is best understood as residing in the community, (ii) the judgments of others count as evidence, and so should change one's own opinion, (iii) subjects would not be better off outside the trial, and (iv) the point of any trial is the resolution of dispute in the medical community. I critically examine these rationales and argue that they are insufficient. Amongst the problems are tensions between various of these underlying rationales, and important ambiguities in just what the CE criterion is to amount to. Finally, I argue that even if use of CE was justified, it would not justify carrying out RCTs anywhere near long enough to discharge our duty to gain reliable knowledge on which to base safe and effective medical practice. Hence, we need some different justification for carrying out RCTs.